Terapi Ketrampilan Sosial Pada Penderita Skizofrenia Di Upt Rehabilitasi Sosial Bina Laras Kediri - Miftahul Nuril Hidayati; Sardjuningsih; Tatik Imadatus Sa’adati (Happiness (Journal of Psychology and Islamic Science), 2020)
The objective of this study is to obtain an overview of the techniques and stages of the implementation of social skills therapy and specific skills that must be possessed by schizophrenics at UPT Rehabilitasi Sosiallocated in the Kras kabupaten Kediri. This research uses clinical psychology approach, descriptive qualitative method. The informants in this study were 5 schizophrenic patients, a social worker, a client mentor, a nurse and a client caregiver who were randomly selected from the data in the Social Rehabilitation Unit, Bina Laras Kediri.This study strives toobtain the techniques and stages of the implementation of social skills therapy in the Social Rehabilitation Unit of Bina Laras Kediri. There are four techniques used un this studi,1) modeling, giving examples repeatedly to clients, 2) role playing, giving the opportunity to clients to practice directly the given modeling, 3) performance feedback, providing reinforcement and 4) transfer training, practicing it in the real world. The results of this study show that there are 3 clients who have the seven categories of social skills and 2 others only have four or five categories of social skills. These seven skills categories are conversation, assertiveness, friendship and dating, community life, conflict management, treatment management, and vocational